The Effect of Field Trip on Biodiversity Knowledge and Environmental Sustainability Attitude of Class X Students of SMA Unggulan Haf-Sa Zainul Hasan BPPT-Genggong - Rahma, Yenny; Suwono, Hadi; Sulisetijono, Sulisetijono (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
The issue of biodiversity is a concern for the whole world today. Education is key in developing knowledge and issues that affect biodiversity in the world. Biodiversity awareness programs are a national responsibility. To achieve this, it is necessary to have knowledge of biodiversity for the community. Inadequate knowledge can affect a person's attitude to the environment. This study aims to determine the influence of field trips on biodiversity knowledge and environmental sustainability attitudes of grade X students of SMA Unggulan Haf-Sa Zainul Hasan BPPT-Genggong. This study was quasi-experimental with a nonrandomized control-group pretest-posttest design. There were 36 students as the experimental group and 36 students as the control group. The results showed that the pretest and posttest data both biodiversity knowledge and environmental sustainability attitudes had normal and homogeneous data, namely with sig. above 0.05. Data analysis with biodiversity knowledge ancova has an F count of 25,674, sig. 0.00 and environmental sustainability attitude has F count 8.757, sig. 0.004. So it can be concluded that learning material on the diversity of living things with the field trip method affects biodiversity knowledge and environmental sustainability attitudes of grade X students of SMA Unggulan Haf-Sa Zainul Hasan BPPT-Genggong.